Chinese adaptation and validation of the chronic rhinosinusitis‐patient‐reported outcome: Assessment of health‐related quality‐of‐life - Chen, Jiani; Hu, Li; Zhang, Chen; Shi, Le; Zhang, Qianqian; Zhou, Yumin; Cheng, Fuying; Gao, Yingqi; Li, Houyong; Wang, Dehui; Wang, Huan; Sun, Xicai (International forum of allergy & rhinology, 2024)
Background The chronic rhinosinusitis patient‐reported outcome (CRS‐PRO) is a recently published disease‐specific questionnaire designed for CRS patients, with fewer entries and ease of completion. This study aimed to translate the CRS‐PRO questionnaire into Chinese and assess its reliability, validity, and responsiveness to provide Chinese patients with a more concise and efficient subjective assessment instrument. Methods The Chinese version of the CRS‐PRO was created through forward‐backward translations and cultural adaptation. Here, 168 CRS patients (118 patients CRS with nasal polyps [CRSwNP] and 50 patients with CRS without nasal polyps [CRSsNP]) and 43 healthy individuals were enrolled. All participants completed the CRS‐PRO, 22‐item Sinonasal Outcome Test (SNOT‐22), and EuroQol five dimensions questionnaire (EQ‐5D) questionnaires preoperatively as well as 3 and 6 months after surgery. Results The Chinese version of the CRS‐PRO demonstrated good internal consistency, with a Cronbach's α of 0.813. It also exhibited a higher criterion validity (r = 0.65, p < 0.05) than the SNOT‐22. A moderate association was found between the CRS‐PRO and objective indicators such as the Lund–Mackay and endoscopic scores. Furthermore, the CRS‐PRO, like the SNOT‐22, could clearly distinguish CRS patients from healthy subjects (p < 0.01), as well as between the CRSwNP and CRSsNP subtypes (p < 0.01). Additionally, changes in the CRS‐PRO exhibited a larger effect size compared to changes in the SNOT‐22 (Cohen's d = 1.05 and 0.93 vs. 0.71 and 0.90 for 3 and 6 months, respectively, all p < 0.01). Conclusions The Chinese version of the CRS‐PRO is a concise, reliable, and responsive instrument that can be utilized as a novel subjective evaluation tool for future clinical practice.